Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex]d = \sqrt{(x_2 - x_1)^{2} + (y_2 - y_1)^{2}} \\d = \sqrt{(3 - (-1))^{2} + (-2 - 4)^{2}} \\d = \sqrt{(3 + 1)^{2} + (-6)^{2}} \\d = \sqrt{(4)^{2} + 36} \\d = \sqrt{16 + 36} \\d = \sqrt{52} \\d = 2\sqrt{13}[/tex]
Answer:
The distance is [tex] 2\sqrt{13} [/tex] units
Explanation:
The distance between two points can be calculated using the following rule:
distance = [tex] \sqrt{(x_{2}-x_{1})^2+(y_{2}-y_{1})^2} [/tex]
The given points are:
(-1,4) representing (x₁,y₁)
(3,-2) representing (x₂,y₂)
Substitute in the formula with the givens to get the distance as follows:
distance = [tex] \sqrt{(3--1)^2+(-2-4)^2} = 2\sqrt{13} [/tex] units
Hope this helps :)
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.